Zoning and forecasting as the basis for sustainable spatial development (on the example of the territories of the Republic of Karelia) - V. Karginova-Gubinova Karginova-Gubinova; A. V. Vasilyeva; M. V. Moroshkina (Модернизация, инновация, развитие)
abstractPurpose: is to develop a methodology for zoning and socio-economic forecasting of the state of the northern and arctic territories in order to produce a conceptual framework to ensure their sustainability.Methods: the work is based on the statistical indicators and rating scores of the spatial development of the territories of the Republic of Karelia, indicators of financial statements of companies operating in the region, and other public information about them for 2010-2021. A number of methods of multivariate statistics, in particular, cluster and regression analysis, mapping method and scenario approach were used to analyze the data.Results: the study shows the importance of zoning and forecasting in the design and implementation of sustainable spatial development policy, as well as the need to update and adapt existing tools to new challenges and characteristics of the regions. The methodology of zoning of territories, based on the existing economic relations between actors and the role of human capital in sustainable development was developed. The methodology of mediumand long-term forecasting of socio-economic space, taking into account  the  mutual influence of adjacent territorial units, was proposed. The methods have been tested for the Karelian Arctic and economically connected territories of the North; a dynamic zoning model has been built. The forecast of mediumand long-term development of this space was carried out with the use of institutional innovations and overcoming of "bottlenecks" by the subjects of management.Conclusions and Relevance: the results obtained can become the basis for the policy of regional development. The paper proposes a conceptual framework of sustainable development strategy for the territories of the Republic of Karelia under consideration. It is shown that one of the fundamental problems of the majority of the northern territories is low human capital characteristics; in this connection a number of institutional changes, in particular, affecting the methodology of calculating social deductions for personal income tax and issuing referrals for targeted training, is proposed. This determines the practical signifi e of the study. The continuation of the work will be the detailing of the policy of sustainable development of Karelia.